HOW TO START YOUR OWN BUSINESS...AND MAKE IT WORK - Rickman, Cheryl; Andrews, John; Byrne, Daniel; Lucas, Sharon; Plowman, Fiona; Setford, Steve; Sienkowska, Lucy; Szudek, Andy; Chadd,Rachel Warren (London, United Kingdom : Dorling Kindersley Limited, 2021)
Discover everything you need to know to turn your big idea into a thriving business with this uniquely visual guide. Combining clear, jargon-free language and bold, explanatory illustrations, How to Start Your Own Business shows you how to develop your ideas into a profitable venture, taking you step by step through everything from business plans to branding. Packed with practical, authoritative advice and graphics that demystify complex topics, such as securing investors, establishing an online presence, and recruiting and managing staff, this book gives you all the tools you need to understand how a modern start-up works, and create your own. Much more than a standard business-management or self-help book, How to Start Your Own Business shows you what other titles only tell you, combining solid reference with no-nonsense advice. It is the perfect primer for anyone with entrepreneurial aspirations, and essential reading for those who simply want to learn more about the world of business and management.
Includes index
Bibliography : pages 212-215
Keywords: New business enterprises -- Management; Success in business; Small business -- Management; Entrepreneurship